Implementation of Halal Supply Chain Management to Achieve Sustainable Performance in the Onion Stick Home Industry - Ferlania, Dianda Aryntya Firia; Rahadian, Yanuar Rafi (Indonesian Journal of Engineering, Science and Technology, 2025)
The onion stick home industry is one of the small-scale food sectors in Indonesia that significantly contributes to local employment and income. Ensuring halal compliance is crucial not only to meet consumer demands but also to enhance sustainable performance. This study aims to examine the implementation of Halal Supply Chain Management (HSCM) and its impact on sustainable performance in the onion stick home industry. Data were collected through surveys and interviews with home industry producers, focusing on four main dimensions of HSCM: halal sourcing, halal production, halal warehousing, and halal distribution. Sustainable performance was measured across economic, environmental, and social indicators. The results indicate that the implementation of HSCM in home industries is moderate, with strong awareness of halal practices but limited formal documentation. Despite these limitations, HSCM positively affects sustainable performance, particularly economic and social aspects. The study also identifies challenges such as limited knowledge of formal halal standards, inadequate documentation, and financial constraints in obtaining halal certification. Strengthening supplier verification, formalizing standard operating procedures, and providing training and government support are recommended to enhance both halal compliance and sustainability. Keywords¾ Halal Supply Chain Management; sustainable performance; home industry; small-scale food industry.